Antioxidant and anti-inflammatory properties of flavonoids from lotus plumule. (30th March 2019) - Chen, Gui-Lin; Fan, Min-Xia; Wu, Jian-Lin; Li, Na; Guo, Ming-Quan
Highlights: The antioxidant and anti-inflammatory mechanisms of flavonoids in lotus plumule were systematically analyzed using radical scavenging assays and ELISA kits. The affinity UF-LC/MS was employed to rapidly screen and identify 12 bioactive flavonoids showing specific binding to COX-2 in lotus plumule. Flavonoids O -glycosides displayed comparable binding affinities to COX-2 compared with flavonoids C -glycosides. Abstract: The antioxidant and anti-inflammatory mechanisms of action of flavonoids in lotus plumule were systematically analyzed using radical scavenging assays and ELISA kits. By this means, flavonoids displayed significant antioxidant activity by donating electron, H atom as well as capturing DPPH and ABTS + free radicals, and anti-inflammatory effect by inhibiting the production of the inflammatory mediators (NO radicals, PGE2 and TNF-α) and pro-inflammatory cytokines (IL-1β and IL-6). Meanwhile, the bioactive components against inflammation targeting COX-2 were also revealed using ultrafiltration coupled to LC-MS (UF-LC/MS). In this way, 12 components showing specific binding to COX-2 were screened out and identified. The structure-activity relationships suggested that flavonoids O -glycosides displayed comparable binding affinities to COX-2 compared with flavonoids C -glycosides and could be considered as the main active components. This study will provide valuable information for the further exploration of lotus plumule as functional foods or in pharmaceutical industries in the near future.